Talent wins : the new playbook for putting people first - Charan, Ram; Barton, Dominic; Carey, Dennis C. (Boston, Massachusetts : Harvard Business Review Press, 2018)
Most executives today recognize the competitive advantage of human capital, and yet the talent practices their organizations use are stuck in the twentieth century. Typical HR talent-planning processes (which are too expensive and take too long to implement) are designed for predictable environments, traditional ways of getting work done, and organizations where'lines and boxes' still define how people are managed. As work and organizations have become more fluid--and business strategy is no longer about planning years out but about sensing and seizing new opportunities and adapting to a constantly changing environment--companies must deploy talent in new ways to remain competitive. Written for CEOs and leaders across the organization, Talent Rules provides a much-needed framework for transforming how companies acquire, manage, and deploy talent--for today's agile, digital, analytical, technologically driven strategic environment--and for creating the HR function the business needs. With examples of companies that are well along the path of reinventing their approaches to talent, such as Amgen, AT&T, BlackRock, GE, Haier, J&J, and PepsiCo, as well as the juggernauts and the start-ups of Silicon Valley, this book provides leaders with a seven-part plan for: Integrating talent and capital Making talent drive strategy Designing and redesigning the work of the organization Scaling up individual talent Creating an M&A strategy for talent Reinventing the role of HR Living the talent agenda Providing deep, expert insight and advice for what needs to change and how to change it, Talent Rules is the definitive book for reimagining and creating the talent-driven organization.--
Intro: Memo to the CEO: your talent playbook -- Forge the tools of transformation -- Energize the board -- Design & redesign the work of the organization -- Reinvent HR as a source of competitive advantage -- Scale up individual talent -- Create an M&A strategy for talent -- Drive the talent playbook.
Keywords: Manpower planning; Ability; Human capital; Business planning; Employee retention; Personnel departments